2001
DOI: 10.1097/00002508-200103000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Physiologic Evaluation of Stellate Ganglion Blockade for Complex Regional Pain Syndrome Type I

Abstract: Clinical investigation is not reliable in the assessment of stellate ganglion blockade. Proof of sympathetically maintained pain based on pain relief after stellate ganglion blockade is not conclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 22 publications
2
56
0
4
Order By: Relevance
“…We and others have shown previously that macro-and microcirculatory changes in the CRPS-I-affected arm resemble the systemic changes in patients with SIRS or sepsis [17][18][19]. Those fi ndings suggest that the profound changes in both macro-and microvascular perfusion in the CRPS-I-affected arm contribute to edema formation and support the hypothesis of an infl ammatory-associated pathogenesis of CRPS.…”
Section: Clinicalsupporting
confidence: 81%
“…We and others have shown previously that macro-and microcirculatory changes in the CRPS-I-affected arm resemble the systemic changes in patients with SIRS or sepsis [17][18][19]. Those fi ndings suggest that the profound changes in both macro-and microvascular perfusion in the CRPS-I-affected arm contribute to edema formation and support the hypothesis of an infl ammatory-associated pathogenesis of CRPS.…”
Section: Clinicalsupporting
confidence: 81%
“…Clinical application of sympathetic blockade has been expanded to patients with hormonal imbalance, psychiatric disorders, and cardiovascular diseases, 27,28 and previous publications have demonstrated that sympathetic blockade can be applied repeatedly without serious adverse effects. 29 We found that monocrotaline treatment led to a significant increase in LF/HF ratio indicating increased sympathovagal balance, whereas SGB attenuated this monocrotaline-induced autonomic balance change. Similar to the previous reports, 13,25 our results also showed that sympathetic hyperactivity is involved in the pathogenesis or progression of PAH, and that the modulation of sympathetic hyperactivity may prevent development or halt the progression of PAH.…”
Section: Discussionmentioning
confidence: 61%
“…Stellate Ganglion Block (SGB) is an effective technique and may be used to manage upper extremities pain due to chronic regional pain syndrome (CRPS) [1,2]. CRPS is a painful and disabling syndrome with physical changes in the affected extremity.…”
Section: Introductionmentioning
confidence: 99%